Mixed drug overdose involving clonazepam, alprazolam, and olanzapine in a 72-year-old male with Parkinson’s disease: a case report - Zhang, Wei; Wang, Mao-Shui; Zhang, Jianguo; Gao, Chunhai (Frontiers in Neuroscience, 2025)
This case report discusses a 72-year-old male patient with Parkinson’s disease, depression, and somatization disorder, presenting to the emergency department after a suspected overdose of clonazepam. The patient was discovered unconscious approximately 2.5 h after ingestion of over 30 tablets of clonazepam, in combination with an overdose of alprazolam and olanzapine. Despite initial challenges with gastric lavage, subsequent treatment involved supportive care, management of complications such as pneumonia, and renal replacement therapy, ultimately leading to recovery. This case highlights the complexities of managing overdoses, particularly those involving drugs with long half-lives, and highlights the challenges of treating elderly patients and the importance of supportive care in recovery.